The Value of Auditor Industry Specialization: Evidence from a Structural Model - Guo, Qiang; Koch, Christopher; Zhu, Aiyong (The Accounting Review, 2022)
ABSTRACT This study investigates the value of auditor industry specialization. In the first step, we use a discrete choice model to derive the first-order demand for auditor industry specialization. Our results reveal that clients have a general preference for auditor industry specialization, relating to both audit firm and audit office specialization. We observe that specializations at the audit firm and audit office level are substitutes. We also find that larger, more complex clients have a stronger demand for industry specialization at the audit office level. In the second step, we use the results from the discrete choice model to quantify the value of auditor industry specialists for clients. We find the overall value of industry specialization aggregated across all clients is 5.2 million USD (0.36 percent of audit fees) and that industry specialization at the firm (office) level is decisive for auditor choice in 4 percent (6 percent) of all cases. JEL Classifications: M42; M48; L11; L84.